Genres of privacy in postwar America - Rampell, Palmer (Stanford, California : Stanford University Press, 2022)
"With this incisive work, Palmer Rampell reveals the surprising role genre fiction played in redefining the category of the private person in the postwar period. Especially after the Supreme Court established a constitutional right to privacy in 1965, legal scholars, judges, and the general public scrambled to understand the scope of that right. Before and after the Court's ruling, authors of genre fiction and film reformulated their aliens, androids, and monsters to engage in debates about personal privacy as it pertained to issues like abortion, police surveillance, and euthanasia. Triangulating novels and films with original archival discoveries and historical and legal research, Rampell provides new readings of Patricia Highsmith, Dorothy B. Hughes, Philip K. Dick, Octavia Butler, Chester Himes, Stephen King, Cormac McCarthy, and others. The book pairs the right of privacy for heterosexual sex with queer and proto-feminist crime fiction; racialized police surveillance at midcentury with Black crime fiction; Roe v. Wade (1973) with 1960s and 1970s science fiction; the Child Abuse Prevention and Treatment Act (1974) with horror; and the right to die with westerns. While we are accustomed to defenses of fiction for its capacity to represent fully rendered private life, Genres of Privacy suggests that we might value a certain strand of genre fiction for its capacity to theorize the meaning of the protean concept of privacy"--
Introduction : the genres of privacy -- The queer art of murder -- Midcentury Black cops -- The science fiction of Roe v. Wade -- A child is being beaten in the 1970s -- Bury me not on the lone prairie -- Conclusion : nothing ever ends.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 17, 2022).
eBooks on EBSCOhost
Keywords: American fiction -- 20th century -- History and criticism; American fiction -- 20th century -- Themes, motives; Fiction genres -- Themes, motives; Privacy in literature; Roman américain -- 20e siècle -- Histoire et critique; Roman américain -- 20e siècle -- Thèmes, motifs; Roman -- Typologie -- Thèmes, motifs; Vie privée dans la littérature.; LITERARY CRITICISM -- American -- General; American fiction; American fiction -- Themes, motives; Privacy in literature; 1900-1999; Privacy; crime fiction; genre; horror; law and literature; post-1945 American literature; science fiction; westerns; Criticism, interpretation, etc; Literary criticism; Literary criticism; Critiques littéraires.